Nature s way: natural predators - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
With growing interest in biological control, it is time to take stock of recent successful experiences in the use of living organisms to prevent or minimise damage caused by insect pests.In Jamaica, a beetle known as the coffee berry borer...